2007
DOI: 10.1126/science.1144581
|View full text |Cite
|
Sign up to set email alerts
|

The Product Space Conditions the Development of Nations

Abstract: Economies grow by upgrading the type of products they produce and export. The technology, capital, institutions and skills needed to make such new products are more easily adapted from some products than others. We study the network of relatedness between products, or 'product space', finding that most upscale products are located in a densely connected core while lower income products occupy a less connected periphery. We show that countries tend to move to goods close to those they are currently specialized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

63
2,200
1
158

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,116 publications
(2,608 citation statements)
references
References 19 publications
63
2,200
1
158
Order By: Relevance
“…S13). Examples of real networks that are similar to a random structure are the network of product space of economic goods 22 and the Internet at the AS level (analysed in Supplementary Section SV).…”
mentioning
confidence: 99%
“…S13). Examples of real networks that are similar to a random structure are the network of product space of economic goods 22 and the Internet at the AS level (analysed in Supplementary Section SV).…”
mentioning
confidence: 99%
“…In Ref. [6] the proximity φ αβ of products α and β was introduced as the symmetrized probability that a country exports product α, given that it exports product β. (2) where C i is the set of products exported by country i, P(α ∈ C i |β ∈ C i ) is the probability of exporting product α given that β is being exported, and φ αβ is the proximity of α and β.…”
Section: International Trade Metricsmentioning
confidence: 99%
“…The countries' future exports are particularly complex to predict, as their evolution depends on many external factors, such as geographical position, diplomatic relations between countries, available natural resources, and technologies. Nevertheless, previous studies [6,13] showed that it is possible to measure the competitiveness of a country, estimate its future growth and even predict its future exports using solely the international trade data. The last aspect, personalized prediction of future exports for each country, further suffers from the lack of a traditional approach with conventional metrics and renowned prediction algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations